PENYELESAIAN HAK ASUH ANAK DALAM KASUS PERCERAIAN STUDI KASUS DI PENGADILAN AGAMA BLITAR PADA PUTUSAN NOMOR 1670/PDT.G/2022/PA.BL - Asrori, Mokhamad; Nurbaedah, Nurbaedah (MIZAN, Jurnal Ilmu Hukum, 2025)
Child custody is a problem that always arises when there is a divorce. Nevertheless, these cases always exist and lead to court. This is what happened in the case at the Blitar Religious Court. namely the Settlement of Child Custody in Divorce Cases in Decision Number 1670/Pdt.G/2022/PA.BL. thus this case becomes important where in the decision considered by the judge considering that child custody falls on the husband as the defendant. While the condition of the child being cared for is at the age of less than 2 years which legally in complications of Islamic law must be under the supervision of the mother. In ayang means the child should be cared for by the mother as the plaintiff. Based on this condition, several indicators emerge which are the focus of this research, namely 1) how the process of child custody is continued and 2) how the judge considers the decision on child custody and what factors are considered in determining child custody.The approach used in this study is to use an empirical juridical approach. Where researchers will conduct various series of studies involving all parties. Both directly related to field studies and literature. In this case what is meant is the decision on Child Custody in Divorce Cases in Decision Number 1670/Pdt.G/2022/PA.BL. The results of this study include: 1), Child Custody Settlement Process, Decision Number 1670/PDT.G/2022/PA.BL at the Blitar Religious Court, refers to a series of processes that present shared evidence P1-P6 as well as T1- T6. In addition to presenting a number of witnesses. Also through a number of stages in the form of mediation until it reaches the trial and ends with a judge's decision. 2), In the judge's decision, there are two things to be considered-first internally and secondly externally. Internally the judge considers the family environment of the plaintiff and the defendant as well as the impact and behavior of both of them on their children. And the second, the judge considers positive law or complications of Islamic law. Thus, the lawsuit filed by the plaintiff against the defendant was rejected because he did not have sufficient evidence and consideration for the benefit of his child. So indirectly the custody of the child goes to the defendant who according to the judge's consideration is more appropriate both in terms of the benefit as well as sufficient evidence and witness testimony.